ANALISIS PENGARUH KEBIJAKAN PENDANAAN DAN LABA DITAHAN TERHADAP NILAI PERUSAHAAN DENGAN SET KESEMPATAN INVESTASI SEBAGAI VARIABEL MEDIASI (STUDI PADA PERUSAHAAN LQ-45 YANG TERDAFTAR DI BEI PERIODE 2009-2013) - Maya Pidna Sari; Yulia Efni; Edyanus Herman Halim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to know the analysis of direct and indirect effect in financing decision and retained earnings mediated by the investment opportunity set to the value of the company at the company LQ-45 listed the Indonesian Stock Exchange in period of the 2009-2013. There were 45 companies in this study that become the population LQ-45 and the sample consisting of 22 companies with the number N of data as much as 110. The sampling technique is based porposive sampling. Analysis of the data use descriptive analysis and path analysis. The result of this study indicates that financing decision effects significantly to investment opportunity set directly, retained earnings influences significantly to investment opportunity set directly, financing decision influence significantly to the value of the company directly, retained earnings effect insignificantly on firm value directly, Investment opportunity set effects significantly to firm value directly. It means that investment opportunity set is capable of mediating the relationship between financing decision and retained earnings to firm value.Keywords: financing decision, retained earnings, investment opportunity set and firm value